Clinical comparison of the effectiveness of 7- and 14-day intracanal medications in root canal disinfection and inflammatory cytokines - Martinho, Frederico C. [UNESP]; Gomes, Cinthya C.; Nascimento, Gustavo G.; Gomes, Ana P. M. [UNESP]; Leite, Fábio R. M. (Springer Nature, 2018)
Objective: This clinical study compared the effectiveness of 7- and 14-day intracanal medications in the reduction of bacteria/endotoxins from primarily infected root canals and determined their antigenicity against macrophages through the levels of cytokines. Methods: Seventy-two primarily infected teeth were randomly divided into six groups according to medication and time of application: 7-day groups = G1, Ca(OH)2 + saline solution (SSL); G2, Ca(OH)2 + 2% chlorhexidine (CHX) gel; and G3, 2% CHX gel and 14-day groups = G4, Ca(OH)2 + SSL; G5, Ca(OH)2 + 2% CHX gel; and G6, 2% CHX gel (all groups, n = 12). Bacterial and endotoxin samples were collected from root canals and inflammatory cytokines of macrophages supernatants. Culture techniques were used to determine bacterial counts and limulus amebocyte lysate (LAL) assay to quantify endotoxins. IL-1β, TNF-α, and PGE2 were measured by ELISA-assay. Results: With regard to the bacterial reduction, no differences were found between all protocols tested (p > 0.05). The CHX protocols (G3 and G6) exhibited the lowest effectiveness against endotoxins (p < 0.05). All protocols were effective in lowering the levels of IL-1β, TNF-α, and PGE2 (p < 0.05), with no difference between the medications tested on days 7 or 14 (p > 0.05). Particularly, the 7-day CHX-protocol (G3) exhibited the lowest effectiveness in lowering the levels of most cytokines compared to the 14-day protocols (G6) (p < 0.05). Conclusions: All the 7- and 14-day intracanal medications were effective in reducing bacteria and endotoxins as well as in lowering the levels of inflammatory cytokines, with CHX showing limited effectiveness against endotoxins. Moreover, 7-day CHX-protocol exhibited the lowest effectiveness in lowering the levels of most cytokines compared to the 14-day protocols. Clinical significance: Seven-day CHX protocol is the less effective protocol and should be carefully applied by the clinician.
Keywords: Calcium hydroxide; Chlorhexidine; Endodontic treatment; Endotoxin; Inflammatory markers